Educational Video SADAR as an Effort to Improve Knowledge about the Risk of Chronic Kidney Failure - Akbar, Ali; Amaludin, Mimi; Alfikrie, Fauzan; Hidayat, Uti Rusdian; Hatmalyakin, Debby; Arisandi, Defa; Nurpratiwi, Nurpratiwi; Safitri, Dewin (Jurnal Keperawatan Profesional (KEPO), 2025)
End-stage renal disease is a global health problem that impacts quality of life and high treatment costs, second only to cardiovascular disease. This study aimed to analyze the effect of the SADAR (Semangat mengAtas dan Sinyal Ancaman Risiko) educational video on efforts to reduce the risk of CKD in the Banjar Sarasan Health Center area, East Pontianak. A quasi-experimental design with a control group was used 44 subjects with hypertension or type II diabetes mellitus who were at risk of developing CKD. The subjects were divided into two groups selected accidentally. The results of the Wilcoxon test showed that the SADAR video (p-value=0,000) and lectures (p=0,000) were both effective in increasing public knowledge about CKD risk detection. The Mann-Whitney test showed that the SADAR video was more effective (p-value=0,015; mean rank=26,77:18,23) than lectures. Further research is needed to evaluate the long-term effectiveness and accessibility of knowledge about CKD risk detection.